Analyze Economic Empowerment of Fisherman Community in Margasari Village, East Lampung - Annissa Valentina; Kusuma Wardany; Sulis Anjarwati (Indonesian Journal of Innovation and Applied Sciences (IJIAS), 2021)
This research aim to know empowerment community of fisherman in Margasari village, Labuhan Maringgai, Lampung Timur. It affected the improvement life quality of the community of fisherman, through participation that means they realized development activity did not only about Government either community participation for quality improvement. This research is field research. Method research that is used in this research is the qualitative approach. Analysis of data used was qualitative with the conclusion of data used inductive. This research indicates that the empowerment level in this village is very low because fisherman did not include in empowerment activity. Most of the fishermen need to be empowered but need a strategy that involved not only one step of implementation but also planning, implementation, until evaluation.